Distribution Network Design and Determination Point of Distribution Center Locations Medical Logistics Assistance Covid-19 in West Java - Muchammad Fauzi; Rienna Oktarina (School of Industrial and System Engineering, Telkom University, 2020)
The distribution of positive Covid-19 cases in Indonesia issued by DKI Jakarta was 3.097 people or45.82%, West Java was 747 people or 11.05%, and Est Java 590 people or 8,73%. Information by PB IDIthere were 24 doctors who died as of April 16, 2020 due to positive Covid-19, 8 from West Java. Problemin Gunung Jati Cirebon Hospital, APD from Health Office of West Java Province is not enough. If eachregion wants to quickly inventory fulfillment, you need a distribution strategy in a fast travel time. Thisstudy discusses the distribution of the network and determines the distribution center of Covid-19 medicallogistical assistance in West Java so that the travelling time for distribution is fast. This study includes thedistribution network design, logistics clustering, and point of distribution center every cluster. The methodused Selective Distribution Channel approach for distribution networks design, K-Means method forclustering, and Gravity Location Model for point placement of distribution center. Based on the result ofthe discussion that can be drawn the conclusion of getting a fast travel time, a distribution networks can bemade with 4 logistics klasters. Cluster 1 in Kasokandel Majalengka, Cluster 2 in Wanaherang GunungPutri, Cluster 3 in Cipendeuy Padalarang, Cluster 4 in Sukamulya Ciamis. The total efficiency of traveltime in cluster 1 is 11.02 hours/week, in cluster 3 is 2.57 hours/week, in cluster 4 os 24.23 hours/week, andin cluster 2 it is not recommended to make distribution center, so distribution on cluster 2 directly fromLanud Halim Perdana Kusumah.